Nutritional targeting of inflammatory pathways and catabolic mediators involved in equine osteoarthritis - Clutterbuck, A. (2011)
Osteoarthritis (OA) is a degenerative disease of synovial joints with an inflammatory component, which affects humans and companion animals, including horses. Current pharmacotherapy for OA is associated with deleterious side effects. Therefore, plant-derived products with anti-inflammatory properties may provide safer natural alternatives. The project aimed to use in vitro models of equine cartilage to test the hypothesis that plant-derived extracts would reduce inflammation and degradation in an explant model of early OA.